Foreign Population and Gambling: Perceptions and Cultural Conditioning: A Qualitative Study in the Area of the Metropolitan City of Milan - Lucchini, Fabio; Gabellini, Eliana; Celata, Corrado (Critical Gambling Studies, 2026)
This paper focuses on the culturally mediated perception of gambling among immigrant communities in the Health Protection Agency of Milan area, and its consequences in terms of health promotion, prevention, and possible access to treatment. Pursuing a gender-balanced approach, 20 semi-structured interviews were conducted with representatives of foreign cultural associations in the area of Milan, involving the six most numerous communities (Egyptian, Romanian, Filipino, Chinese, Peruvian and Albanian). A textual and thematic analysis of the emerging content was conducted following the grounded theory approach and considering the complex interplay between agency and structural constraints. From the interpretation of the categories and macro-categories identified, it emerges how the perceptions of gambling and gambling disorder (GD) by the foreign communities considered are culturally conditioned, raising questions about the role of family and community in relation to individual agent. This highlights the desirability of outlining culturally sensitive health promotion, prevention and treatment programs that can impact risk behaviors and possibly facilitate the seeking of professional help.